A Detoxification Enzyme for Apis mellifera Newly Characterized by Recombinant Expression: 10-Formyl Tetrahydrofolate Dehydrogenase - Mating, Moritz; Sharbati, Soroush; Einspanier, Ralf (Frontiers in Insect Science, 2022)
Honey bees are important managed pollinators that perform important ecological and economic functions. In recent decades, the obligate ectoparasite Varroa destructor severely affected survival of honey bees, as it either feeds on hemolymph and fat bodies or acts as a vector for viruses. A common treatment against the varroa mite is formic acid, which has been used for many years by beekeepers. This treatment is known to be effective, but the therapeutic index is very narrow. Many beekeepers report negative effects of formic acid on bees, which include damage to brood, worker bee mortality and queen loss. Little is yet known about the molecular mechanisms of formic acid detoxification in honey bees. Our previous study showed the upregulation of a predicted 10-formyl tetrahydrofolate dehydrogenase (10-FTHFDH) transcripts in honey bees exposed to formic acid. Here, the predicted honeybee-specific 10-FTHFDH has been recombinantly expressed and its hydrolase and dehydrogenase activities were investigated. As a result, the enzyme shows similar dehydrogenase activity in comparison to known 10-FTHFDHs. This study provides further knowledge to better understand the detoxification mechanisms of formic acid in Apis mellifera.